Familial Mediterranean Fever Mimicking Wilson's Disease: A Case Report - Caner Turan; Miray Karakoyun; Çiğdem Ömür Ecevit; Funda Yılmaz; Sema Aydoğdu (Galenos Yayinevi, 2018)
Wilson's disease (hepatolenticular degeneration) is an autosomal recessive defect in cellular copper transport. Impaired biliary copper excretion leads to an accumulation of copper mostly in the liver, brain and cornea. Familial Mediterranean Fever (FMF) is an autosomal recessive autoimmune disease as a result of a mutation in the MEFV gene encoding pyrin protein characterized by recurring fever and polyserositis attacks. In this report, we describe a Turkish female child with cholestatic hepatitis of unknown etiology who was later diagnosed with typical FMF.